Implant Survival and Function Ten Years After Kinematically Aligned Total Knee Arthroplasty - Howell, Stephen M.; Shelton, Trevor J.; Hull, Maury L. (The Journal of arthroplasty, 2018)
Alignment in the varus or valgus outlier range of the tibial component, knee, and limb might adversely affect the long-term results of kinematically aligned total knee arthroplasty (TKA) particularly when patients are selected without restricting the degree of preoperative varus-valgus and flexion deformity. A retrospective review of all patients treated in 2007 with a primary TKA determined the 10-year implant survivorship, yearly revision rate, Oxford Knee Score, and WOMAC. All 222 knees (217 patients) were aligned kinematically using patient-specific instrumentation without restricting the degree of preoperative deformity and with the restoration of the native joint lines and limb alignment. Mechanical alignment criteria categorized the alignments of the tibial component, knee, and limb as in-range or in a varus or valgus outlier range. The implant survivorship (yearly revision rate) was 97.5% (0.3%) for revision for any reason and 98.4% (0.2%) for aseptic failure. The percentage postoperatively aligned in the varus outlier (valgus outlier) range was 78% (0%) for the angle between the tibial component and mechanical axis of the tibia, 31% (5%) for the tibiofemoral angle of the knee according to the criteria by Ritter et al, and 7% (21%) for the hip-knee-ankle angle of the limb according to the criteria by Parratte et al. Patients grouped in the varus outlier range, valgus outlier range, and in-range had similar implant survival and function scores. The 10-year Oxford Knee Score (48 best) and WOMAC (0 best) averaged 43 and 7 points, respectively. With the limitation that a large case series unlikely represents the full range of preoperative deformities and native alignments, treatment of patients with kinematically aligned TKA with patient-specific instrumentation without restricting the preoperative deformity did not adversely affect the 10-year implant survival, yearly revision rate, and level of function. Level III, therapeutic study.